FEATURES OF QUALITY-MANAGEMENT POLICIES IN GEORGIA - Batiashvili, Ioseb (European Scientific Journal, ESJ, 2016)
World global processes led to development of international trade in modern era. More attention was paid to product quality together with trade development. A non government organization - ISO was launched in 1947, in order to develop unified standards for quality management throughout the world. Economy of Georgia has been in transition for past 24 years. Transformations have had highly fractured characteristics during these years, A single politics of development could not be conducted during this period. Economical and political courses are altered in line with every change of government and this situation in turn affects business environment.